Retrospective evaluation of perioperative and short term clinical outcomes in appendicular long bone skeleton fractures repaired via the string of pearls (SOP) locking plate system - Field, Matthew R. (BMC Vet Res, 2018)
BACKGROUND: Internal plate fixation and, more recently, locking plate fixation are commonly used in the repair of fractures in small animal surgery. This retrospective study reviewed the use of the String of Pearls locking plate system in the fixation/repair of appendicular long bone skeleton fractures in 31 small animal veterinary patients (33 fractures). RESULTS: Major complications necessitating revision surgery occurred in 7/33 (21%), with implant failure as the inciting cause in all cases. Variables corresponding to an unsuccessful outcome were evaluated, and a correlation was found with plates placed in a bridging manner (placed without rigid anatomic reconstruction, p = 0.02) and length of follow-up (p = 0.01). CONCLUSIONS: The SOP plating system can be used in the repair of appendicular longbone skeletal fractures, however, the authors propose that adjunct fixation, such as intramedullary pin, double plating, or external coaptation would likely improve results and should be considered imperative in cases in which anatomic reconstruction is either not desirable or achievable. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12917-018-1707-6) contains supplementary material, which is available to authorized users.